Spontaneous community-acquired bacterial meningitis in adults admitted to the intensive care units in the Caribbean French West Indies: Unusual prevalence of Klebsiella pneumonia. (November 2020) - Piednoir, Pascale; Clarac, Ulrich; Rolle, Amélie; Bastian, Sylvaine; Gruel, Gaelle; Martino, Frédéric; Mehdaoui, Hossein; Valette, Marc; Breurec, Sébastien; Carles, Michel
Highlights: Epidemiology of spontaneous bacterial meningitis vary in tropical areas. Klebsiella pneumoniae (Kp) in the Caribean, including K1 or K2 capsular serotypes. Hypervirulent (Hv) strains in patients with predisposing risk factors. Extended spectrum beta-lactamase - and carbapenemase-producing HvKp. Abstract: An unusual prevalence of Klebsiella pneumoniae (24%) was observed in 25 adults admitted to the intensive care units of two University Hospitals in the French West Indies, for spontaneous community-acquired bacterial meningitis. All tested isolates had several prominent features of hypervirulent isolates, including rmpa and iuc genes, K1 or K2 capsular serotypes.